2008
DOI: 10.3138/utlj.58.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Federal Judicial Appointments: A Look at Patronage in Federal Appointments Since 1988

Abstract: The article investigates whether the new screening system introduced by the federal government in 1988 for appointing judges (below the Supreme Court level) has reduced the influence of patronage in the federal judicial appointment process. To analyse this question, we examined whether judicial appointees from 1989 through 2003 donated to a political party, particularly the party that appointed them, up to five years prior to their appointment. We found that almost one-third of appointees had donated to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For instance, 28.2 per cent of judges who were elevated and 45.2 per cent of judges who were given administrative promotions had major direct activities or major connections, compared to 22.4 per cent in our overall dataset. The numbers were fairly consistent between Conservative governments~Mulroney 1988-1993and Harper 2006-2008! and Lib-eral governments~Chrétien 1993-2003and Martin 2004 The numbers also tended to reflect the general provincial patterns discussed above, though one notable exception was Ontario, which featured a noticeably higher percentage of partisans being provided elevations and administrative appointments compared to "regular" appointments.…”
Section: Elevations and Promotionsmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, 28.2 per cent of judges who were elevated and 45.2 per cent of judges who were given administrative promotions had major direct activities or major connections, compared to 22.4 per cent in our overall dataset. The numbers were fairly consistent between Conservative governments~Mulroney 1988-1993and Harper 2006-2008! and Lib-eral governments~Chrétien 1993-2003and Martin 2004 The numbers also tended to reflect the general provincial patterns discussed above, though one notable exception was Ontario, which featured a noticeably higher percentage of partisans being provided elevations and administrative appointments compared to "regular" appointments.…”
Section: Elevations and Promotionsmentioning
confidence: 73%
“…For example, in 1998 there was a story published about a friend of then Justice Minister Anne McLellan being appointed in Nova Scotia after the screening committee was asked to reassess its initial finding of "not recommended"~Meek, 1998!. Until now, more systematic examinations of the impact of the 1988 screening committees on appointments were confined mostly to tracing whether individuals had donated money to the party in power prior to their appointment by the federal government~Forcese and Freeman, 2005;Schmitz, 2005!. In 2008, using a more rigorous method of classifying appointees as "probable" donors than previous studies, we found that 30.6 per cent of appointees from 1989 to 2003 very likely had donated to their appointing party in the five years prior to their appointment.…”
Section: Previous Assessments Of the Screening Committee Processmentioning
confidence: 99%
“…In order to consider how party interests may affect judicial appointments, party donations by judicial appointees are used as a proxy for party connection. While this approach follows other studies (Forcese and Freeman, 2005;Riddell et al, 2008), this measure does have limitations that should be acknowledged. First, the depth of party connections in judicial appointments is unlikely to be captured by party donations alone.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of party connection on the selection of judges has long been a reality in Canada (Russell, 1987). While the appointment of blatantly underqualified party loyalists is no longer a concern in the way it was a few decades ago (Russell and Ziegel, 1991), recent scholarship has shown that party connection remains a prominent feature among the women and men chosen by the federal government to serve as judges (Forcese and Freeman, 2005; Hausegger et al, 2010; Riddell et al, 2008). Participation in a political party is not necessarily a negative attribute for a judicial candidate to possess.…”
mentioning
confidence: 99%
“…The federal government in Canada made adding women to the bench more of a priority after the introduction of the screening committees. Approximately one-third of appointees to the provincial appellate courts from 1989 to 2003 were women (Riddell et al, 2008).…”
Section: Judicial Process Selection and Decision Makingmentioning
confidence: 99%